Microbes Go to School: Using Microbiology and Service-Learning to Increase Science Awareness and Fostering the Relationship Between Universities and the General Public - Fatton, Mathilda; Schneiter, Arthur; Allisiardi, Miriam; Hänni, Lola; Hauser, Gilles; Gonçalves-Fernandes, Yazalde; Pessina, Alice; Pijnenburg, Marie-Lou; Vaudroz, Clément; Bshary, Andrea; Bindschedler, Saskia; Junier, Pilar (Frontiers in Education, 2021)
Microbiology is an essential element of our everyday lives. This is not only the consequence of the importance of some pathogenic microorganisms, but also due to their positive and important role in processes related to human health, food production or waste recycling, to cite a few. However, the relevance of microbiology for the wellbeing of humankind and the planet still needs to reach beyond academic circles. Many current matters of urgency, such as environmental pollution or climate change, could partly be tackled by using green and sustainable solutions derived from microbial biotechnologies. Nevertheless, the wider public still attributes a negative connotation to microbes (such as fungi and bacteria). The aim of this study was to implement service-learning as a pedagogical approach to increase scientific and microbiology literacy in society. Service-learning is a teaching and learning strategy that integrates community service and civic responsibility, fostering the dissemination of scientific knowledge. We are using this approach to communicate about pressing societal issues surrounding microbes (antibiotic resistance, natural resources recycling, human microbiota, and food production among others) to an audience of pupils attending public schools. The activity of service-learning is proposed in the final year of the biology bachelor curriculum. Its purpose is to allow university students to develop and practice their lay communication skills as a key competence to be acquired during their university education. In the activity, the students develop their own concept and material for the activity and deliver it to pupils at primary and secondary school levels (pupils aged 6-15 years old). The message is also expected to be disseminated beyond the participants, when the students and pupils share their experience with family and friends. With this pedagogical approach, we intend to raise awareness regarding the importance of microbiology and its dual roles as harmful and beneficial for humans. We also wish to increase the connection between primary, secondary and tertiary educational institutions. Finally, we want to highlight the importance of having a new generation of communication savvy professionals in biology.